The law and economics of the environment - Heyes, Anthony, 1967-; Edward Elgar Publishing (Cheltenham, U.K. ; Northampton, Mass. : E. Elgar, 2001)
This outstanding book focuses on how economics can contribute to the design, implementation and appraisal of legal systems that create the "right" incentives for environmental protection. The sixteen original and specially commissioned contributions -- written by some of the leading names in their field--span many of the important areas of contemporary interest and employ case study material combined with theoretical, empirical and experimental research.
1. Law and economics of the environment : an overview -- 2. Coasean bargaining in collaborative environmental policy -- 3. The vertical extension of environmental liability through chains of ownership, contract and supply -- 4. Horizontal vicarious liability -- 5. Liability policy and toxic pollution releases -- 6. The economics of clean-up and implications for legal design -- 7. Environmental liability in practice : liability for clean-up of contaminated sites under superfund -- 8. Self-enforcement of environmental law -- 9. The theory of penalties : "leverage" and "dealing" -- 10. Criminal law as an instrument of environmental policy : theory and empirics -- 11. Citizen suits -- 12. Law versus regulation : a political economy model of instrument choice in environmental policy -- 13. International harmonization of environmental law : theory with application to the European Union -- 14. Insurability, environmental risks and the law -- 15. Environmental damages in court : the American trader case -- 16. Protest, property rights and hazardous waste : a reassessment.
Includes bibliographical references (p. 387-389) and index.
Keywords: Environmental law -- Economic aspects; Law and economics; Electronic books